Recruitment for Health Disparities Preventive Intervention Trials: The Early Childhood Caries Collaborating Centers - Tiwari, Tamanna (Centers for Disease Control and Prevention, 2014)
BACKGROUND: Four trials of interventions designed to prevent early childhood caries are using community-engagement strategies to improve recruitment of low-income, racial/ethnic minority participants. The trials are being implemented by 3 centers funded by the National Institute of Dental and Craniofacial Research and known as the Early Childhood Caries Collaborating Centers (EC4): the Center for Native Oral Health Research at the University of Colorado, the Center to Address Disparities in Children’s Oral Health at the University of California San Francisco, and the Center for Research to Evaluate and Eliminate Dental Disparities at Boston University. COMMUNITY CONTEXT: The community contexts for the EC4 trials include urban public housing developments, Hispanic communities near the US–Mexican border, and rural American Indian reservations. These communities have a high prevalence of early childhood caries, suggesting the need for effective, culturally acceptable interventions. METHODS: Each center’s intervention(s) used community-based participatory research approaches, identified community partners, engaged the community through various means, and developed communication strategies to enhance recruitment. OUTCOME: All 3 centers have completed recruitment. Each center implemented several new strategies and approaches to enhance recruitment efforts, such as introducing new communication techniques, using media such as radio and newspapers to spread awareness about the studies, and hosting community gatherings. INTERPRETATION: Using multiple strategies that build trust in the community, are sensitive to cultural norms, and are adaptable to the community environment can enhance recruitment in underserved communities.